TASKS ON THE DEVELOPMENT OF SPEAKING COMPETENCE (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This article focuses on the importance of developing speaking competence in language learners and presents various tasks that can be incorporated into language teaching to enhance this skill. The article provides an overview of the key components of speaking competence and highlights the benefits of incorporating task-based learning approaches. Additionally, it presents five practical tasks that can be used to develop speaking competence, including role-plays, debates, information gap activities, problem-solving tasks, and presentations. These tasks are designed to promote fluency, accuracy, and confidence in oral communication. Overall, this article aims to provide language teachers with valuable insights and practical techniques for fostering speaking competence in their students.